Pelatihan Implementasi Strategi Metakognitif Dalam Pembelajaran Bahasa Inggris Daring/Bauran Pada Guru MTs - Rina Husnaini Febriyanti; Hanna Sundari (CV. Multi Kreasi Media, 2022)
The community service was conducted in MTs Al Falah Al Anshoriyah with the address in Jl. Dukuh V No.1A, RT.2/RW.5, Dukuh, Kec. Kramat jati, Kota Jakarta Timur, Daerah Khusus Ibukota Jakarta,Indonesia, and aimed to provide a training of implementing metacognitive strategy specifically in online English Language Teaching/ Learning. The main activity of this community service shared and highlighted the knowledge regarded to metacognitive strategy that was explored in conceptually and practically understanding for the teachers in MTs Al Falah Al Anshoriyah. The employed method in this activity was Community Language Learning which pointed the discussion process among the participants to obtain the teachers’ voices in confirming their pedagogical or experience issues and related to the training topic. Due to the pandemic condition, activities were carried out online through the Zoom conference media. The results and implications of this activity to the teachers were to gain new insights on how to apply and build metacognitive strategies for their students, especially in online/blended learning.